Implant programs affect performance and quality grade - Christopher D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2010)
Selection of dosage, timing, and number of anabolic implants continues to be a source of controversy for feed yard managers and their consultants. Although the dose-dependent effects on performance are fairly well accepted, impacts on carcass quality continue to be debated. This study was intended to summarize effects of different implant programs on performance and carcass quality on the basis of a cross section of available published research.
Keywords: Cattlemen& #x27; s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen& #x27; s Day; Beef; Implants; Performance; Quality grade; Carcass traits